Evaluasi dan redesain geometrik jalan pada Jalan Raya Denpasar-Gilimanuk Segmen Ruas Antosari - Batas Kota Tabanan (KM 34+100-KM 34+422) - I Made Agus Ariawan; Putu Cinthya Pratiwi Kardita; I Putu Chandra Wibawa; Putu Kwintaryana Winaya; I Putu Mahendi Krisna Massudana (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
Traffic accidents often occur due to a mismatch between road geometry and vehicle operating conditions, particularly on high-risk road sections. This study aims to evaluate road geometric conditions and design improvements for the Denpasar-Gilimanuk Highway, specifically at accident-prone locations, namely the Antosari–Tabanan City Border road segment (KM 34+100–KM 34+422). The research methodology began with data collection, including an inventory of road geometry, traffic data, and accident records. The evaluation and design of road geometry were conducted in accordance with Road Geometric Design Guidelines No. 13/P/BM/2021. The existing road geometry consists of a compound curve with radius (R) of 30 m and 120 m, without a connecting straight section, with a lane width of 6.7 m. The maximum grade (g) is 7%, with vertical curve lengths of 60 m and 80 m. These values do not meet minimum standards, thus potentially increasing the risk of accidents. The geometric redesign was carried out with two alternatives: either making it a single curve with an adjusted curve radius (R) of 130 m or 110 m and a vertical alignment gradient of 4.86% or 6.54%, with curve lengths of 150 m or 90 m, based on considerations of stopping sight distance, headlight glare, leading sight distance, and driving comfort. The design also includes widening the pavement at the curve by 1.25 m, improving roadside drainage, and installing traffic signs and road markings. This research contributes to providing a comprehensive approach in handling accident-prone locations through the integration of geometric aspects and road equipment.